PELAKSANAAN URUSAN PEMERINTAHAN DALAM PEMELIHARAAN JALAN OLEH DINAS PEKERJAAN UMUM DAN PENATAAN RUANG (PUPR) DI KOTA PEKANBARU TAHUN 2018 - Jefri Ermon; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Roads are the basic infrastructure infrastructure that humans need to be able to move from one location to another in order to fulfill needs, either as a land vehicle transportation route or distribution of goods and services. The formation of Law Number 23 of 2014 concerning Regional Government aims to provide services in terms of providing public facilities needed by the community such as building and improving roads in Pekanbaru City. Therefore, the City Government, through the Public Works and Spatial Planning Office, is authorized to provide these services to the community. This study aims to describe the implementation of concurrent government affairs in the Highways Sector at the Public Works and Spatial Planning (PUPR) Office in road maintenance and the inhibiting factors of the Highways Sector in road maintenance in Pekanbaru City in 2018. The research location was conducted at the Public Works and Pekanbaru City Spatial Planning. Data collection techniques used are through interviews and documentation. The results of this study are that the roles of the Highways Division of Pekanbaru City have not been maximized in carrying out their duties and functions in road maintenance, this can be seen from the total length of 1,277,900 Km roads in Pekanbaru City in 2018, only 46.196% which is categorized as Good. This means that 53.914% of roads are still damaged and maintenance must be carried out at these road points. Some of the inhibiting factors that are often experienced by the DGH sector in road maintenance are budget constraints, limited human resources, and lack of facilities and infrastructure. Of course this greatly affects the performance results of the Highways Division itself. Keywords: Government Affairs, Maintenance, Public Works Service and Spatial Planning, Road Maintenance.